PARENTAL AUTONOMY SUPPORT AND CHILD PSYCHOSOCIAL ADJUSTMENT: EXAMINING THE ROLE OF CULTURAL HIERARCHY - Saïb, Naïla; Joussemet, Mireille; Cavenaghi, Anna; Robichaud, Jean-Michel; Mageau, Geneviève A.; Koestner, Richard (International Journal of Child, Youth and Family Studies)

(untitled) (University of Victoria, 2024)
The studies described in this paper investigated whether cultural hierarchy plays a moderating role in the association between parental autonomy support and child psychosocial adjustment, employing samples presenting a wide range of cultural variability (parents born in 71 different nations). The participants’ cultural backgrounds, based on the parents’ birth country, were rated in terms of emphasis on hierarchical power using Schwartz’s dimensional coding system. Structural equation modelling analyses revealed no moderation effect of cultural hierarchy on the relation between parental autonomy support and child outcomes, with the exception of the relation between parental autonomy support and adolescents’ autonomous self-regulation. As expected, parental autonomy support and cultural hierarchy were significantly and negatively correlated. Parental autonomy support was often associated with indicators of youth psychosocial adjustment, whereas cultural hierarchy was generally unrelated to adjustment. These results support self-determination theory’s position on the universal benefits of autonomy support.